Temperature-induced misfolding in prion protein: evidence of multiple partially disordered states stabilized by non-native hydrogen bonds - Chamachi, Neharika G.; Chakrabarty, Suman (Biochemistry, 2017)
The structural basis of pathways of misfolding of a cellular prion (PrPc) into the toxic scrapie form (PrPsc) and identification of possible intermediates (e.g., PrP*) still eludes us. In this work, we have used a cumulative us of replica exchange molecular dynamics simulation data to construct the conformational free energy landscapes and capture the structural and thermodynamic characteristics associated with various stages of the thermal denaturation process in human prion protein. The temperature-dependent free energy surfaces consist of multiple metastable states stabilized by non-native contacts and hydrogen bonds, thus rendering the protein prone to misfolding. We have been able to identify metastable conformational states with high beta-content (similar to 30-40%) and low alpha-content (similar to 10-20%) that might be precursors of PrPsc oligomer formation. These conformations also involve participation of the unstructured N-terminal domain, and its role in misfolding has been investigated. All the misfolded or partially unfolded states are quite compact in nature despite having large deviations from the native structure. Although the number of native contacts decreases dramatically at higher temperatures, the radius of gyration and number of intraprotein hydrogen bonds and contacts remain relatively unchanged, leading to stabilization of the misfolded conformations by non-native interactions. Our results are in good agreement with the established view that the C-terminal regions of the second and third helices (H2 and H3, respectively) of mammal prions might be the Achilles heels of their stability, while separation of B1-H1-B2 and H2-H3 domains seems to play a key role, as well.

Two-dimensional infrared spectroscopy reveals cosolvent-composition-dependent crossover in intermolecular hydrogen bond dynamics - Kashid, Somnath M.; Jin, Geun Young; Chakrabarty, Suman; Kim, Yung Sam; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2017)
Cosolvents have versatile composition-dependent applications in chemistry and biology. The simultaneous presence of hydrophobic and hydrophilic groups in dimethyl sulfoxide (DMSO), an industrially important amphiphilic cosolvent, when combined with the unique properties of water, plays key roles in the diverse fields of pharmacology, cryoprotection, and cell biology. Moreover, molecules dissolved in aqueous DMSO exhibit an anomalous concentration-dependent nonmonotonic behavior in stability and activity near a critical DMSO mole fraction of 0.15. An experimental identification of the origin of this anomaly can lead to newer chemical and biological applications. We report a direct spectroscopic observation of the anomalous behavior using ultrafast twodimensional infrared spectroscopy experiments. Our results demonstrate the cosolventconcentration-dependent nonmonotonicity arises from nonidentical mechanisms in ultrafast hydrogen-bond-exchange dynamics of water above and below the critical cosolvent concentration. Comparison of experimental and theoretical results provides a molecular-level mechanistic understanding: a distinct difference in the stabilization of the solute through dynamic solute solvent interactions is the key to the anomalous behavior.

Thermodynamic view of dynamic allostery in a PDZ domain protein - Kumawat, Amit; Chakrabarty, Suman (Biophysical Journal, 2019)